A Systematic Review of Tools Assessing the Perspective of Caregivers of Residents With Dementia. (April 2022) - Harper, Alexandra E.; Rouch, Stephanie; Leland, Natalie E.; Turner, Rose L.; Mansbach, William E.; Day, Claire E.; Terhorst, Lauren
In collaboration with stakeholders, we conducted a systematic review of psychometric evidence for self-report tools measuring the perspective of family caregivers of nursing home residents with dementia. Our rationale for this review was based on evidence that nonpharmacological interventions can ameliorate dementia symptoms in nursing home residents. Such interventions require caregiver participation, which is influenced by perspectives. Yet, no existing tool measures the multidomain caregiver perspective. Our review followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol. The final sample included 42 articles describing 33 tools measuring domains of nursing home dementia care such as behavioral and psychological symptoms of dementia, resident quality of life, dementia-specific knowledge, communication, and medication use. We uncovered evidence gaps for tools measuring dementia-specific knowledge, communication, and medication use, all of which were important to our stakeholders. Future research should focus on development of psychometrically sound tools in alignment with the multidomain caregiver perspective.